2022
DOI: 10.3390/diagnostics12081797
|View full text |Cite
|
Sign up to set email alerts
|

Ampullary Large-Cell Neuroendocrine Carcinoma, a Diagnostic Challenge of a Rare Aggressive Neoplasm: A Case Report and Literature Review

Abstract: Ampullary large-cell neuroendocrine carcinomas (LCNECs) are extremely rare, and available data are limited on case reports. They present with jaundice, non-specific abdominal pain, or weight loss, imitating adenocarcinoma. Their incidence increases due to the improved diagnostic techniques. However, preoperative diagnosis remains challenging. We report the case of a 70-year-old man with a history of metabolic syndrome, cholecystectomy, and right hemicolectomy, presenting with jaundice. Laboratory results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Studies have shown a steadily rising age-adjusted incidence rate in small intestinal NETs. The highest incidence was in the population between 70 and 79 years, and the lowest was between 20 and 29 years; however, no cases were reported <20 years of age [ 4 , 9 , 10 ]. The patient in this case presented at the age of 18 years with symptoms of abdominal pain and jaundice suggestive of biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown a steadily rising age-adjusted incidence rate in small intestinal NETs. The highest incidence was in the population between 70 and 79 years, and the lowest was between 20 and 29 years; however, no cases were reported <20 years of age [ 4 , 9 , 10 ]. The patient in this case presented at the age of 18 years with symptoms of abdominal pain and jaundice suggestive of biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy registry analysis from Sweden reported a mean annual incidence of 5.33 per 100,000 individuals [ 1 ]. Ampullary NETs are extremely rare and represent less than 0.3% of all gastroenteropancreatic neuroendocrine neoplasms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the prognosis and management of GEP-NENs, the Ki-67 labelling index and mitotic count are critical indicators of the state of tumor proliferation [ 14 , 15 ]. The WHO classifications of NENs have been updated from previous classifications differentiating neuroendocrine tumors (NETs) and poorly differentiated neuroendocrine carcinoma (NECs), according to the Ki-67 index and mitotic count [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%